Penerapan Green Accounting Terhadap Profitabilitas Pada PT Unilever Indonesia Tbk - Fitri Sulistiyana; Ajeng Rossantika Sari; Maria Yovita R Pandin (Institut Teknologi dan Bisnis (ITB) Semarang, 2023)
This research has the goal of analyzing the application of green accounting which has the ability to act as an environmental cost and environmental performance with a profit level. The research object being studied at this time is PT Unilever Indonesia Tbk which uses a descriptive qualitative method where the data collection comes from the company's annual report distributed by the Indonesia Stock Exchange (IDX). The environmental cost variable has no effect on the profit level, the environmental performance variable has no effect on the profit level. This study aims to improve Green Accounting in the application of company profitability.